2017
DOI: 10.1007/s00216-017-0323-9
|View full text |Cite
|
Sign up to set email alerts
|

A green analytical chemistry approach for lipid extraction: computation methods in the selection of green solvents as alternative to hexane

Abstract: There is a great interest in finding alternatives and green solvents in extraction processes to replace petroleum based solvents. In order to investigate these possibilities, computational methods, as Hansen solubility parameters (HSP) and conductor-like screening model for real solvent (COSMO-RS), were used in this work to predict the solvation power of a series of solvents in salmon fish lipids. Additionally, experimental studies were used to evaluate the performance in lipids extraction using 2-methyltetrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 31 publications
3
51
0
Order By: Relevance
“…Furthermore, a higher MAG content was detected in ethyl lactate extract (8.10%) than hexane (2.24%). These solvents have a high boiling point which could affect their efficiency and induce lipid degradation (Cascant et al, 2017).…”
Section: Experimental Solvent Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a higher MAG content was detected in ethyl lactate extract (8.10%) than hexane (2.24%). These solvents have a high boiling point which could affect their efficiency and induce lipid degradation (Cascant et al, 2017).…”
Section: Experimental Solvent Screeningmentioning
confidence: 99%
“…Also, they are biodegradable, non-toxic and non-flammable. Indeed, many studies have shown the potential of alternative solvents for lipid extraction instead of hexane (Sicaire et al, 2015;Breil et al, 2016;Cascant et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CPME is an excellent alternative for replacingc holoroform in such extraction strategies. In as imilar study, [60] different bio-solvents were assessed for the extraction of components from salmon fish oil, whichi se specially rich in longchain Omega-3 polyunsaturated fatty acids (LCn-3PUFAs). Again, theoretical data from HSPs indicated the effectiveness of CPME in solvating all lipid components of this oil, being more specific than the other solvents evaluated for each lipid class.…”
Section: Introduction:m Otivation For Eco-friendly Solvents and For Cpmementioning
confidence: 99%
“…Moreover, it is biodegradable . Recently, bio‐based solvents including MeTHF, limonene and p ‐cymene have been found to be effective to extract lipids from several plant seeds . Some green methods including ultrasonic assisted extraction have been applied to extract volatiles compounds from carvi .…”
Section: Introductionmentioning
confidence: 99%